Удмурты. Наследие древних воршудов - Грязев Георгий Геннадьевич (Удмуртия, 2022)
Экземпляры: ЦБ (20230504) / Инвентарный номер: 56579 / Цена: 600.00 / Сис.шифр: 63.5(2Рос.Удм) / Авт.знак: У 30 / ГРНТИ: 03.23 / ББК: 63.5(2Рос.Удм)